PRABOWO SUBIYANTO’S LEGAL POLITICAL DIRECTION: CRITICAL DISCOURSE ANALYSIS ON LAW ENFORCEMENT IN THE FIRST DEBATE OF THE 2024 PRESIDENTIAL ELECTION - Khoiron, Khoiron; Syaifudin, Ahmad (Universitas Padjadjaran, 2025)
This article examines how presidential candidates have produced legal discourses that are used as political instruments in winning the political contestation of the Indonesian national presidential election in 2024. Through political discourse, Prabowo Subiyanto aimed to influence the public for his victory. As a result, he emerged victorious, proving that political discourse in public debates can successfully deconstruct, influence, and steer the way of thinking and can lead voters’ preferences. The main argument in this article is that discourse as a political instrument is not empty, but behind the discourse is a form of political truth operation produced for certain goals. In this study, the method used is qualitative with discourse analysis to uncover the ideal of truth behind discourse. The researcher applied Van Dijk’s discourse theory which uses three analyses; text, social cognition and social context. Therefore, the use of Van Dijk’s critical analysis method is the author’s position as a novelty in the midst of several discourse studies that emphasise more on content analysis. Based on the results of this study, the researcher found several results from the direction of legal politics, namely that it offers law as a priority, law enforcement and economic growth, independence of law enforcers, and law based on the principle of justice.